2012
DOI: 10.1111/ejn.12050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic amphetamine treatment and acute withdrawal on serotonin synthesis and clearance mechanisms in the rat ventral hippocampus

Abstract: Amphetamine withdrawal in both humans and rats is associated with increased anxiety states, which are thought to contribute to drug relapse. Serotonin in the ventral hippocampus mediates affective behaviors, and reduced serotonin levels in this region are observed in rat models of high anxiety, including during withdrawal from chronic amphetamine. This goal of this study was to understand the mechanisms by which reduced ventral hippocampus serotonergic neurotransmission occurs during amphetamine withdrawal. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 78 publications
2
29
1
Order By: Relevance
“…Instead, we observed an increase in stress-induced corticosterone levels in the ventral hippocampus during amphetamine withdrawal when compared to saline pretreated controls. The reduced stress-induced serotonergic response observed during amphetamine withdrawal, using the same stress paradigm as used here (Li et al, 2014), may instead be explained by a combination of reductions in ventral hippocampus glucocorticoid receptor levels (Barr and Forster, 2011) and increased extracellular serotonin reuptake (Barr et al, 2013), both of which have been observed in the ventral hippocampus following the same amphetamine treatment and withdrawal paradigm used here. It is also possible that surgical and microdialysis procedures may have altered glucocorticoid function in the ventral hippocampus.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Instead, we observed an increase in stress-induced corticosterone levels in the ventral hippocampus during amphetamine withdrawal when compared to saline pretreated controls. The reduced stress-induced serotonergic response observed during amphetamine withdrawal, using the same stress paradigm as used here (Li et al, 2014), may instead be explained by a combination of reductions in ventral hippocampus glucocorticoid receptor levels (Barr and Forster, 2011) and increased extracellular serotonin reuptake (Barr et al, 2013), both of which have been observed in the ventral hippocampus following the same amphetamine treatment and withdrawal paradigm used here. It is also possible that surgical and microdialysis procedures may have altered glucocorticoid function in the ventral hippocampus.…”
Section: Discussionmentioning
confidence: 91%
“…Dialysate levels were not corrected for differences in probe recovery. To account for this, dialysate levels were expressed as the % of the average of the baseline samples (Barr et al, 2013; Dorey et al, 2012; Droste et al, 2008, 2009a; Keeney et al, 2006; Li et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local infusion of the selective serotonin reuptake inhibitor paroxetine was employed, because we previously showed that expression of the serotonin transporter (SERT - the substrate for paroxetine) in the ventral hippocampus is not affected by amphetamine pretreatment and withdrawal (Barr et al, 2013). In addition, paroxetine infused directly into the ventral hippocampus of amphetamine pretreated rats undergoing withdrawal raises extracellular 5-HT levels to the same degree as in saline pretreated rats (Barr et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, rats going through amphetamine withdrawal fail to demonstrate corticosterone-induced or stress-induced extracellular 5-HT release within the ventral hippocampus (Barr and Forster, 2011, Li et al, 2014) at the same withdrawal periods when increased anxiety-like behavior is observed (Barr et al, 2010, Vuong et al, 2010). Furthermore, amphetamine withdrawal is associated with reduced glucocorticoid receptor expression and increased expression of organic cation transporters type 3 (OCT 3) in the ventral hippocampus, that latter of which clear extracellular 5-HT (Barr and Forster, 2011, Barr et al, 2013). Combined, these molecular changes are thought to lead to dampened extracellular 5-HT levels in response to stress during amphetamine withdrawal (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%